La orientación sexual como secuela de la violencia sexual - Guamán Bacacela, Nathalia Elvira (2024)
Sexual violence causes traumas of great emotional impact that significantly affect the overall well-being of people, therefore, the effects are varied: it affects the academic, social and affective area, and also alters the psychosexual development. The main objective of this research work was to describe the scientific evidence of sexual orientation as a sequel of sexual violence and, specifically, to describe the psychoemotional and psychosexual effects of sexual violence and to identify the origin and psychobiological development of sexual orientation, as a proposed solution, an informative guide was developed with the purpose of strengthening prevention measures aimed at parents and caregivers to protect children from sexual violence. Regarding the methodology, a qualitative non-experimental longitudinal approach was used, with a descriptive scope based on the bibliographic synthesis. The study population was based on all articles with scientific evidence published in databases such as Scielo, Google Scholar, Dialnet and Science Direct, taking into account the inclusion and exclusion criteria, 31 scientific studies were selected, from which the main result was that sexual violence affects sexual orientation, although not in a determinant way, since this has a psycho-biological origin and development. Finally, these findings underlie the importance of making an informative guide with the objective of strengthening prevention measures focused on parents and caregivers in order to protect their sons and daughters from sexual violence